Proliferasi Kalus dari Eksplan Hipokotil dan Kotiledon Tanaman Jarak Pagar (Jatropha curcas L.) pada Pemberian 2,4-D - Zulkarnain, Zulkarnain; Lizawati, Lizawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The aim of this study was to develop an efficient method for the induction of embryogenic callus formation for in vitro propagation ofjatropha. Plant materials used were 30-days old in vitro seedlings, cut into hypocotyl and cotyledon (lower, middle and upper) sections.Medium used was MS composition supplemented with vitamins, 3% sucrose, 0.7% agar at pH 5.8 ± 1, and 2,4-D (0, 1, 2, 3, 4 dan5 mg l-1). Cultures were kept at temperature of 25 ± 1 0C with 50 μmol m-2 s-1 light intensity and 16-h photoperiod. The results indicated thatthe rate of callus formation depended on the source of explant, the application of 2,4-D, and the interaction of both. The fastest callusproliferation (2.33 days following initiation) was obtained on cotyledon explants cultured on medium without 2,4-D. The explant sourcesand 2,4-D concentrations also showed significant effect on the percentage of explant forming callus. The most callus formation (88.33%)was obtained on middle cotyledon cultured on 3 mg l-1 2,4-D, whereas the fewest (6.84%) was found on upper cotyledon cultured on mediumwithout 2,4-D. The colour of callus was dominated by white, light yellow, cream and brown with mostly compact structure, particularly onhypocotyl cultured on medium without 2,4-D. The texture of callus formed on hypocotyl treated with up to 4 mg l -1 2,4-D was dominatedby coarse appearance. In contrast, majority of callus proliferated on hypocotyl treated with 5 mg l -1 2,4-D or cotyledon treated with orwithout 2,4-D produced callus with smooth texture %.